2020
DOI: 10.1021/acs.jproteome.0c00725
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites in the TCA Cycle Promote Resistance to Chloramphenicol of Edwardsiella tarda

Abstract: Antibiotic-resistant bacteria are a serious threat to human and animal health. Metabolite-enabled eradication of drugresistant pathogens is an attractive strategy, and metabolite adjuvants, such as fumarate, are used for restoring the bactericidal ability of antibiotics. However, we show that metabolites in the TCA cycle increase the viability of Edwardsiella tarda against chloramphenicol (CAP), based on the survival assay of differential metabolites identified by LC-MS/MS. Furthermore, NADPH promotes CAP resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…Exogenous glucose restores the sensitivity of Vibrio alginolyticus to gentamicin [48]. Metabolites in the TCA cycle promote Edwardsiella tarda resistance to chloramphenicol [49]. In this study, exogenous palmitic acid promoted the resistance of X. oryzae to ZS, whereas triclosan potentiated ZS to kill Xoo-Rzs.…”
Section: Discussionmentioning
confidence: 52%
“…Exogenous glucose restores the sensitivity of Vibrio alginolyticus to gentamicin [48]. Metabolites in the TCA cycle promote Edwardsiella tarda resistance to chloramphenicol [49]. In this study, exogenous palmitic acid promoted the resistance of X. oryzae to ZS, whereas triclosan potentiated ZS to kill Xoo-Rzs.…”
Section: Discussionmentioning
confidence: 52%
“…The metabolic status of bacteria was found to play a crucial role in mediating resistance ( Zhang et al, 2019 ; Chen et al, 2022 ; Kok et al, 2022 ; Zheng et al, 2022 ). Moreover, exogenous metabolites including carbohydrates, amino acids, and nucleotides were found to modulate antibiotics susceptibility and bactericidal effects of antibacterial drugs by metabolic reprogramming in Gram-negative bacteria ( Peng et al, 2015a ; Peng et al, 2015b ; Su et al, 2015 ; Wu et al, 2015 ; Ye et al, 2018 ; Wang et al, 2020 ; Chung et al, 2022 ). Metabolites present several advantages as adjuvants for antibiotics as they are inexpensive, non-toxic, and slow to induce resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites in the TCA cycle promoted resistance to chloramphenicol of E . tarda (Wang, Dong, et al, 2021). TAM, the translocation and assembly module, was found and identified as a necessary factor for pressure resistance and virulence (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that Glu6P transport regulatory protein UhpA played a role in regulating the virulence gene expression (Ye et al, 2021). Metabolites in the TCA cycle promoted resistance to chloramphenicol of E. tarda (Wang, Dong, et al, 2021). TAM, the translocation and assembly module, was found and identified as a necessary factor for pressure resistance and virulence (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%